Genotypic variations in agro-morphological and physico-chemical traits in ethnic aromatic rice (Oryza sativa) landraces of Odisha - DIKSHIT, NILAMANI; SIVARAJ, NATARAJAN; DAS, ANATH BANDHU (The Indian Journal of Agricultural Sciences, 2014)
Nineteen traditional aromatic rice (Oryza sativa L.) varieties of Odisha, India were assessed for morphological, agronomical, biochemical and cooking characteristics to identify superior genotypes for breeding with regard to quality characters. Significant variability was observed in morphological, agronomical and cooking characteristics among the rice varieties. Kalajira (IC 355057) had maximum number of grains per panicle (204 numbers) with high fertility (89.12%). Hence, this could be used as donor for improvement of indigenous aromatic varieties for higher productivity. Badsahbhog and Basumati possessed the intermediate alkali value and amylose content. Chatianaki possessed long kernel length after cooking and high elongation ratio. Gyanbhog showed high hulling, milling and head rice recovery. Therefore, the head rice recovery of Gyanbhog and amylose content of Basumati (23.5%) could be used as donor plants in rice improvement programmes.